2012
DOI: 10.1038/ncomms2295
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin reverses impaired social interaction in mouse models of tuberous sclerosis complex

Abstract: Impairment of reciprocal social interaction is a core symptom of autism spectrum disorder. Genetic disorders frequently accompany autism spectrum disorder, such as tuberous sclerosis complex caused by haploinsufficiency of the TSC1 and TSC2 genes. Accumulating evidence implicates a relationship between autism spectrum disorder and signal transduction that involves tuberous sclerosis complex 1, tuberous sclerosis complex 2 and mammalian target of rapamycin. Here we show behavioural abnormalities relevant to aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
179
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(188 citation statements)
references
References 56 publications
5
179
1
3
Order By: Relevance
“…These cognitive abnormalities emerged in the absence of neuropathology and seizures (Ehninger et al 2008(Ehninger et al , 2009. A recent study by Sato et al (2012) in TSC mutant adult mice found that impaired social behavior also reversed by mTOR inhibitor treatment, which associated with mTOR inhibition at the molecular level. Others have also provided evidence that autistic-like behavior can be prevented with mTOR treatment in mouse models of TSC (Tsai et al, 2012;Talos et al, 2012;Reith et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…These cognitive abnormalities emerged in the absence of neuropathology and seizures (Ehninger et al 2008(Ehninger et al , 2009. A recent study by Sato et al (2012) in TSC mutant adult mice found that impaired social behavior also reversed by mTOR inhibitor treatment, which associated with mTOR inhibition at the molecular level. Others have also provided evidence that autistic-like behavior can be prevented with mTOR treatment in mouse models of TSC (Tsai et al, 2012;Talos et al, 2012;Reith et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Rett syndrome, fragile X syndrome and tuberous sclerosis complex exhibit comorbidity with ASDs, and their corresponding mouse models were established and extensively studied [16][17][18][19] . Rescue experiments using these syndromic ASD mouse models successfully identified key molecular pathways involved in the pathology of neural circuits and behavioural deficits [9][10][11][20][21][22] . However, most ASD cases are non-syndromic, and recent genetic studies of non-syndromic ASDs identified a large number of candidates with rare genetic variants 6,7 .…”
mentioning
confidence: 99%
“…Эксперимен-тальные модели туберозного склероза убедительно демонстрируют, что нарушения mTOR играют клю-чевую роль в формировании социального поведения и обучения [14]. Короткий курс рапамицина не толь-ко восстанавливал синаптическую пластичность, но и уменьшал нарушения поведения у эксперимен-тальных животных [15].…”
Section: в помощь практическому врачуunclassified